Design, Synthesis, Single X-Ray Crystal Structure, DFT and Molecular Docking Studies of Novel Clip Type-Pyridyltetrazole Analogues - Babu, M. Surendra; Reddy, K. Santhosh; Ghosh, Kalyan Sundar; Sahoo, Bijaya Ketan; Himasekar, Ch.; Mustafa, Shaik (Asian Journal of Chemistry, 2018)
Novel clip type-pyridyltetrazole analogs of 1,3-bis(5-(pyridin-2-yl)-1H-tetrazol-1-yl)propan-2-ol (3A) and 1,3-bis(5-(pyridin-2-yl)-2H-tetrazol-2-yl) propan-2-ol (3B) have been synthesized by the reaction of 2-(1H-tetrazol-5-yl)pyridine (2) with 0.5 equivalent of epichlorohydrine in DMF using K2CO3 as a base. Relevant monomers of 1-chloro-3-(5-(pyridin-2-yl)-1H-tetrazol-1-yl)propan-2-ol (3C) and 1-chloro-3-(5-(pyridin-2-yl)-2H-tetrazol-2-yl)propan-2-ol (3D) have been synthesized by reaction of compound 2 with one equivalent of epichlorohydrine in DMF using K2CO3 as a base. The compounds 3C and 3D are further modified by the reaction sequences to obtain the ligands 1-(2-(hydroxymethyl)phenoxy)-3-(5-(pyridin-2-yl)-1H-tetrazol-1-yl)propan-2-ol (3G) and 1-(2-(hydroxymethyl)phenoxy)-3-(5-(pyridin-2-yl)-2H-tetrazol-2-yl)propan-2-ol (3H) respectively. The eight synthesized compounds (3A-3H) were characterized by 1H NMR, 13C NMR, IR and Mass spectroscopy. The compound 3A, was crystallized in triclinic primitive system space group P2(1)/c with a = 8.9442 Å, b = 9.2097 Å, c = 11.3558 Å, V = 814.68 Å, R1 = 0.0213 at 298 K. The compounds 3A and 3B were optimized, HOMO/LUMO and molecular electrostatic potential studies were carried by DFT calculations with B3LYP/6.311G** method. The molecular docking studies were performed on 3A, 3B, 3G and 3H and the studies reveal that all the compounds exist in crescent shapes.